The Adaptive Evolution and Gigantism Mechanisms of the Hadal “Supergiant” Amphipod Alicella gigantea - Li, Wenhao; Wang, Faxiang; Jiang, Shouwen; Pan, Binbin; Chan, Jiulin; Xu, Qianghua (Frontiers in Marine Science, 2021)
Hadal trenches are the deepest areas in the ocean with high hydrostatic pressure and very low food supplies. Amphipods are considered dominant scavengers in the hadal food webs. Alicella gigantea is the largest hadal amphipod, and, as such, attracted a lot of attention. However, the adaptive evolution and gigantism mechanisms of the hadal “supergiant” remain unknown. Here, the whole body transcriptome analysis regarding two hadal amphipods, the largest-sized A. gigantea from the New Britain Trench and the small-sized Bathycallisoma schellenbergi from the Marceau Trench were conducted. Size and weight measurement of the two hadal amphipods revealed that A. gigantea grew comparatively much faster than B. schellenbergi. Phylogenetic analyses showed that A. gigantea and B. schellenbergi clustered into a Lysianassoidea clade, distinct from the Gammaroidea which consisted of shallow-water Gammarus species. Codon substitution analyses revealed that “Response to Starvation”, “Glycerolipid Metabolism” and “Meiosis” pathways were enriched among the two hadal amphipods positively selected genes (PSGs), suggesting that hadal amphipods are subjected to intense food shortage and those pathways are the main adaptation strategies to survive in the hadal environment. To elucidate the mechanisms underlying the gigantism of A. gigantea, small-sized amphipods were used as the background for evolutionary analysis, we found the seven PSGs, which were ultimately related to growth and proliferation. In addition, the evolutionary rate of the GO term “Growth Regulation” was significantly higher in the A. gigantea than that of the small-sized amphipods. Combined together, those points might be the possible gigantism mechanisms of the hadal “supergiant” A. gigantea.